Adopting FIDIC 2017 Red Book Extension of Time Procedure for Construction Projects in UAE - BDAIWI, YAMAN MUSTFA (2018)
It has been concluded by several studies that EOT claims are among the most disputed issues in the construction industry due to lack, misunderstanding, or wrong application of relevant contract provisions. In the case of escalation to litigation path, the UAE CTC will be the framework upon which the ruling will be based. This will also be another potential area of further dispute as the concept and mechanism of EOT claim evaluation is not clearly identified in the CTC and thus it will be depending mainly on the expert report. This problem becomes more visible when dealing with other EOT issues such as the most suitable impact analysis method, total float ownership or concurrent delay. Therefore, construction professionals usually resort to using standard form of contracts such as FIDIC to overcome these shortcomings. Even though the EOT procedure is more elaborated in the FIDIC 1999 red book in which it provides a better EOT procedure than when relying on simply drafted bespoke contract, it was concluded in the dissertation that similar issues such as impact analysis method, total float ownership and concurrent delay are still be disputed under the this standard form of contract. The study then evaluated the same procedure under FIDIC 2017 red book to confirm whether it is a better alternative than the previous version. It was concluded that in the new FIDIC edition, issues of impact analysis method and total float ownership were dealt with more clearly than the previous version. The same was concluded for the case of concurrency expect that (1) there is an apparent conflict between Sub-Clause 8.5 and Sub-Clause 17.2, and (2) the construction professionals participated in the study survey were not in agreement with the method proposed in Sub-Clause 8.5. The participants in the survey were also in favor of the new agreement procedure prior to make any determination as proposed by FIDIC new edition. Accordingly, the study concluded that though the FIDIC 2017 red book seems to be providing a better EOT procedure, a precaution must be taken when drafting the particular conditions in regards to the concurrent delay and impact analysis method. In addition, particular conditions should not be drafted in a way that might appear to be in conflict to the UAE CTC, as in the case of adhesion clauses, given the fact that the judge has the authority of nullifying it if the dispute was not resolved amicably.